José Martí and Paulo Freire: Approaches for a Reading of the Critical pedagogy - Miguel Alvarado Arias (Universidad Autónoma de Baja California, 2007)
The research establishes moments of approximation between the pedagogic ideas of José Martí and Paulo Freire, considering the lecture of the critic pedagogy.  Initially the sense of this focus is explained.  Subsequently, with texts from both authors, an integrative proposal on its philosophical-pedagogical thought is built.  The current thinking of the authors are valued and confronted with some post-modern statements, which discredits the production of speeches that, with critical look, they reflect on the asymmetric relations and the consequences of the globalization among uneven worlds.